2000
DOI: 10.1515/znb-2000-0515
|View full text |Cite
|
Sign up to set email alerts
|

Enaminouraciles as Precursors for Synthesis of Pyrimido[4,5-a]pyrimidine- 2,4-diones

Abstract: The reaction of 6-aminouracil 1 with formaldehyde and secondary amines in ethanol at room temperature gave the corresponding 5-alkylaminomethyl derivatives (2a-c) and bis(4- pyrimidyl) methane (4). Also, Mannich reaction with primary aliphatic and aromatic amines at room temperature afforded pyrimid[4,5-d]pyrimidine (5 and 6). Treatment of 1 with o-phenylenediamine through transamination gave com pound 7 which cyclized through intramolecular Mannich reaction with formalin to yield pyrimido[4,5-e]-[l,4]diazepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Recently, we noted that the reactions of 6-amino-1,3dimethyluracil with primary amines and formaldehyde have been used for preparations of pyrimido [4,5-d]pyrimidine-2,4diones. 30 It was found that stirring a mixture of 6-amino-1-(2chlorobenzyl)uracil 8 with an equimolar amount of a primary aromatic or aliphatic amine and excess of formalin in the presence of acetic acid at room temperature affords 5,6,7, 8-tetrahydropyrimido [4,5-d] pyrimidine-2,4(1H,3H)-dione (11) in good yield (Scheme 3) but 8-hydroxymethyl derivative of 11 was not obtained as reported earlier. 29 This conclusion was supported by the following evidence, in the 1 H NMR spectra of compounds 11a-d no signals for an 8-CH2OH group were found.…”
mentioning
confidence: 99%
“…Recently, we noted that the reactions of 6-amino-1,3dimethyluracil with primary amines and formaldehyde have been used for preparations of pyrimido [4,5-d]pyrimidine-2,4diones. 30 It was found that stirring a mixture of 6-amino-1-(2chlorobenzyl)uracil 8 with an equimolar amount of a primary aromatic or aliphatic amine and excess of formalin in the presence of acetic acid at room temperature affords 5,6,7, 8-tetrahydropyrimido [4,5-d] pyrimidine-2,4(1H,3H)-dione (11) in good yield (Scheme 3) but 8-hydroxymethyl derivative of 11 was not obtained as reported earlier. 29 This conclusion was supported by the following evidence, in the 1 H NMR spectra of compounds 11a-d no signals for an 8-CH2OH group were found.…”
mentioning
confidence: 99%
“…Furthermore, the interesting Psychopharmacological activity of benzodiazepine [26,27] enthused us to synthesize the 5,10 (20). Compound 20 has been obtained through cyclocondensation of 5 with 1,2-bis(chloromethyl)benzene [28].…”
Section: Resultsmentioning
confidence: 99%
“…A number of biological significant compounds were used to regulate the growth of plants in their protection area [20]. These studies revealed the introduction of expedient methods to synthesize pyrimido [4,5-d]pyrimidine-2,4-dione [21]. Now a days, pyrimido-pyrimidines (annulated uracil) is a very interesting class of compounds as they display a large number of pharmacological activities with their effective inhibitory characteristics about tyrosine kinase area for the receptors of epidermal growth [22], dihydrofolate-reductase [23] and 5-phosphoribosyl-1pyrophosphate synthetase [24].…”
Section: Introductionmentioning
confidence: 99%